Odpowiedź :
Odpowiedź:
(2x - 1)^2 - (2x+3)^2=y
(2y - 1)(2y+1)+96=4y(y+3)+x
4x^2 - 4x+1 - (4x^2+12x+9)=y
4y^2 - 1+96=4y^2+12y+x
4x^2 - 4x+1 - 4x^2 - 12x - 9=y
4y^2 - 4y^2 - 12y - x= - 96+1
- 16x - y=8 /*( - 12)
- x - 12y= - 95
192x+12y= - 96
- x - 12y= - 95
192x - x= -96 - 95
191x= - 191 /:191
x= - 1
- 16x - y=8
-16*( - 1) - y=8
16 - y=8
- y=8 - 16
- y= - 8 /:(-1)
y=8
x= - 1
y=8
spr
(2*( - 1) - 1)^2 - (2*( - 1)+3)^2=8
(2*8 - 1)(2*8+1)+96=4*8(8+3)+( - 1)
( - 2 - 1)^2 - ( - 2+3)^2=8
(16 - 1)(16+1)+96=32*11 - 1
( - 3)^2 - 1^2=8
15*17+96=352 - 1
9 - 1=8
255+96=351
8=8
351=351
Szczegółowe wyjaśnienie:
[tex]\begin{cases}(2x-1)^2-(2x+3)^2=y\\ (2y-1)(2y+1)+96=4y(y+3)+x\end{cases}\\\\\begin{cases}4x^2-4x+1 -(4x^2+12x+9) =y\\ 4y^2-1 +96=4y^2+12y+x\end{cases} \\\\\begin{cases}4x^2-4x+1 -(4x^2+12x+9) =y\\ 4y^2-1 +96=4y^2+12y+x\end{cases}\\\\\begin{cases}4x^2-4x+1 - 4x^2-12x-9=y\\ 4y^2 -4y^2-12y-x=-95\end{cases}\\\\\begin{cases}4x^2-4x - 4x^2-12x -y=8\\ -12y-x=-95\end{cases}[/tex]
[tex]\begin{cases} -y-16x =8\ \ |*(-12)\\ -12y-x=-95\end{cases}\\\\\begin{cases} 12y+192x =-96\\ -12y-x=-95\end{cases}\\---------\\191x=-191\ \ |:(-191)\\x=-1 \\\\ -y-16x =8\\ -y-16 *(-1) =8 \\-y+16=8 \\-y=8-16\\-y=-8\ \ |*(-1)\\y=8\\\\\begin{cases}x=-1\\y=8 \end{cases}[/tex]